2013
DOI: 10.1080/08832323.2011.638680
|View full text |Cite
|
Sign up to set email alerts
|

The Evaluation of MBA Group Work: A Case Study of Graduate Student Experiences and Perceptions of Positive Group Work Outcomes

Abstract: The article forms part of an exploration into how graduate business students experience group work. A single-case, embedded study was conducted in 2010-2011, and reveals new insight and understanding into the manner in which master's of business administration students perceive evaluation methods of their group work assignments and how these methods contribute to their perception of positive group work outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 44 publications
(64 reference statements)
0
15
0
Order By: Relevance
“…Researchers and educators have found that group work projects result in a) the enhancement of student learning through constructive educative processes, b) the development of students' critical thinking and problem solving abilities, and c) an interdependence among group members that facilitates learning of collaborative work skills (Alden 2011; Cameron et al 2009;Isaac 2012;Jensen et al 2012;Payne et al 2006;Rafferty 2013;Scherling 2011). However, participation in group-work can include both negative cognitive and affective consequences for students (Isaac 2012;Neu 2012;Yamane 1996).…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations
“…Researchers and educators have found that group work projects result in a) the enhancement of student learning through constructive educative processes, b) the development of students' critical thinking and problem solving abilities, and c) an interdependence among group members that facilitates learning of collaborative work skills (Alden 2011; Cameron et al 2009;Isaac 2012;Jensen et al 2012;Payne et al 2006;Rafferty 2013;Scherling 2011). However, participation in group-work can include both negative cognitive and affective consequences for students (Isaac 2012;Neu 2012;Yamane 1996).…”
Section: Introductionmentioning
confidence: 92%
“…This is in part because instructors often lack adequate information to provide the individuals in group projects a grade that accurately reflects their participation (Alden 2011;Dommeyer 2012). Alternatively, some instructors elect to use peer evaluation process, where input from students is used to adjust individual students' grades (Rafferty 2013). This shifts the burden of grading in part to students who due to the social costs, may be reluctant to provide negative feedback of their peers.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Longer exposure to using a mobile app may help a student further learn how their group members perceive them (Rafferty, 2013). Collecting two waves of data allowed for testing the impact of the T1 independent variables on the T2 team process outcomes.…”
Section: Limitations and Future Research Implicationsmentioning
confidence: 99%